Factors associated with premenstrual syndrome of emergency nurse: A multicenter study in China - Yiqian Chen; Xin Yang; Xiaodan Li; Xiaoting Wei; Lianhua Bai (BMJ Publishing Group, 2022)
Objective: To study the factors associated with premenstrual syndrome (PMS) in emergency department (ED) nurses. Methods: A multicenter cross-sectional study was conducted in female ED nurses in China. Data gathering questionnaires included the Daily Record of Severity of Problems, Chinese Nurses Stressor Scale, Social Support Rating Scale, and Self-Rating Anxiety Scale. All questionnaires were used to assess the symptoms prospectively over 2 months. Results: A total of 289 ED nurses were recruited. The incidence of PMS was 67.47%. The most common symptoms were tiredness (76.90%), anger (76.90%), restlessness (75.40%), snoring (69.20%). Univariate analysis showed that the BMI and occupational stress score was significantly higher, and the age was significantly younger in the PMS group compared with the non-PMS group. According to the multiple linear regression, the symptoms of PMS were positively associated with the occupational stress score and anxiety score, and negatively with the level of education received. Conclusions: occupational stress, anxiety, and education level may associated with the occurrence of PMS in ED nurses.